The (im)possibility of inclusion : reimagining the potentials of democratic inclusion in and through activist music education - Laes, Tuulikki (Taideyliopiston Sibelius-Akatemia, 2017)
This dissertation examines inclusion as an ambiguous concept and practice within the context of music education in Finland. The general ethos of inclusive education aims to ensure equal opportunities for all students. However, social practices that are mediated through action and structures within music education contexts, such as segregating students into categories of those who are able, and those who are in need of special education, therapy, or care, generate paradoxes of what inclusion means, and for whom. Furthermore, in the Finnish context the system of music schools has a tradition of selecting young and talented students, with the objective of guiding them toward professional music careers. Such approaches to music education make, in Bourdieusian terms, a distinction between those in the targeted mainstream, and those who are outside of this ideal because of their age, ability, or other characteristics, thus overlooking equal possibilities for learning and gaining agency in and through music. The research project builds upon four sub-studies, which are reported in international, refereed journal articles, focusing on the Resonaari music school which promotes inclusive and accessible music education within the Finnish music school system. By utilizing methodological strategies for reflexive interpretation, these sub-studies examine and reflect on the complexity of inclusion from varying perspectives. The first sub-study presented the case of six female older adults who construct their musical agency within a rock band context at Resonaari, examining the wider meanings assigned to rock band music learning with regard to personal empowerment and a deepened understanding of aging. The second sub-study examined how teacher activism is enacted at Resonaari through innovative pedagogical practices, ethical commitment, and flexible policy advocacy. The third sub-study investigated student music teachers' reflections upon workshops run by Resonaari's musicians, aiming to expand the discourse on professionalism by addressing disability as a generative notion for diversity within higher music education. Finally, the continuum of the sub-studies culminated in the researcher's self-reflexive narrative of striving toward activist scholarship during the research project, addressing the challenges and potentials of inclusive research in music education. Through the methodological lens of critical reflexivity, the overarching task of this research project was to examine: How might Resonaari's activist practices disrupt the hegemonic social practices and discourses of music education; and what potential might these ruptures hold for the reconstruction of the structural, ethical, and political enactments of inclusion? The theoretical framework builds on John Dewey's pragmatist philosophy of educational democracy and moral imagination, as well as complexity theories. Drawing upon Gert Biesta's conceptualization of democratic inclusion, it is argued here that there is a continuing need to challenge the understandings and discourses of inclusion through extending the scope of transformational activism within music education. The findings of this research indicate the benefit of recognizing the potential of inclusivity, as exemplified by Resonaari's specialized music education context, as both a generative and ambiguous process. By identifying the implicit and explicit, and the transferable and unique, these manifestations of inclusion revealed the complexity of such discourses and practices. This expanded and problematized view of inclusion is termed activist hope in this dissertation. Hence, by considering democracy as an experiment, we may radically challenge, extend, and reconstruct the envisioning and implementations of inclusive music education.
Keywords: aktivismi; demokratia; erityiskasvatus; ikääntyneet; inkluusio; musiikkikasvatus; musiikkioppilaitokset; refleksiivisyys; vammaisuus; MuTri